A three-dimensional mesoscale model for progressive time-dependent deformation and fracturing of brittle rock with application to slope stability. (July 2021) - Yuan, Yang; Xu, Tao; Heap, Michael J.; Meredith, Philip G.; Yang, Tianhong; Zhou, Guanglei
Abstract: An understanding of progressive time-dependent deformation is essential for determining appropriate measures to ensure the long-term integrity of rock-masses surrounding engineering structures. We propose a 3D numerical model, that uses the Norton-Bailey creep law and a time-independent damage evolution law, to investigate the progressive time-dependent deformation and fracturing of brittle rock. The model considers material heterogeneity and the concept of mesoscopic renormalization at the mesoscale. The cooperative interaction between microcrack distribution and damage evolution leads to local material degeneration as a function of increasing time in the model. First, the input parameters for the model were calibrated and the model was validated using laboratory experiments. Numerical creep simulations were then performed for a range of constant stresses. Our model can accurately replicate the evolution of strain and strain rate as a function of time, the output of acoustic emission energy, and the emergence of a macroscopic failure plane seen in laboratory experiments. Our simulations also show that the minimum creep strain rate and the time-to-failure increase and decrease, respectively, as stress is increased, also seen in laboratory experiments. For example, increasing the differential stress by 10 MPa increased the minimum creep strain rate increased by an order of magnitude. Finally, we use the proposed 3D model to investigate the time-dependent stability of an engineering-scale rock slope containing faults at the Fushun West Open Pit coal mine. A small increase in fault-adjacent damage was observed after 40 days and, between 60 and 120 days, the damage on the side of the slope increased. After 140 days, the localized growth of the damaged elements split the slope into two segments, resulting in slope failure. Our 3D numerical model highlights potential slope instability in the Fushun West Open Pit coal mine and can be used to investigate slope stability in engineering projects worldwide.